Teaching Creativity To Communities In The Middle Of A Digital Knowledge Culture - Rahman, Mohammad Taufiq; Anwar, Rully Khairul (SOSIETAS, 2020)
Indonesian society has entered a period of mass and competitive knowledge production through the Internet boom. However, to produce beneficial results requires separate methods. For this reason, there are collaborative government efforts with contemporary art and communication workers to bring the community to creative arts endeavors. Using semi-structured interviews with seven creative entrepreneurs and 14 trainees, this research explores the experiences of teachers and students of creative products and activities, especially focusing on how they work together in the learning process. The themes of commercialization and the development of networks emerged, challenging creative knowledge practitioners to monetize. The trainees are not a homogeneous group. This research makes Bandung a model city in Indonesia which has a high enough creative culture to be evaluated and improved pragmatically. Interactions that arise before and after the Bandung Creative Hub can be identified the difference through the accuracy of the delivery of information through the appropriate target audience, equipment and communication facilities between creative actors, and budget conditions in meeting the needs of arts and creativity training. Some of the supporting factors for teaching creativity are the interaction between creative actors and the community, through the participants' interest in the activities carried out by the creators, how to deliver good information, the fabric of cooperation relationships and the completeness of supporting facilities. The efforts made by the creators to maintain the relationship are by the stage they capture potential people, the stage of lasting relationships and the stage of providing rewards to the community in the form of direct contributions.